Agua, ¿para qué y para quién? - Sagredo Aylwin, María Paz (Pontificia Universidad Católica del Perú, 2025)
The article analyzes how the discourses and demands of actors involved in agricultural activities in the Coquimbo Region (Chile), among the peasant organizations, trade associations of medium-sized and large producers and public organizations, reflect different views and tensions regarding water scarcity product of the decrease in precipitations and the system of access and distribution of water for irrigation. Using elements of political ecology and discourse analysis, we seek to understand how actors elaborate their discourses on water scarcity and how they adapt other discourses on the topic based on their own interests. The article concludes that, although there are common elements and concepts in all discourses, these reflect different demands and tensions among local producers, and between them and public services. In the case of peasant organizations, water scarcity is addressed as a threat to a rural way of life, from the business sphere it is conceived as a threat to food production and exportation, and for public organizations it is addressed as a risk to environmental sustainability and food security and sovereignty.

El artículo analiza de qué manera los discursos y demandas de los actores involucrados en la actividad agropecuaria en la región de Coquimbo (Chile), entre ellos, organizaciones campesinas, asociaciones gremiales de medianos y grandes productores y los organismos públicos, reflejan distintas posiciones y tensiones en torno a la situación de escasez hídrica que experimenta la zona producto de la disminución de precipitaciones y del modelo de acceso y distribución de agua para riego. Tomando elementos de la ecología política y el análisis de discursos, se busca comprender de qué manera los actores construyen sus discursos respecto a la situación de escasez hídrica y cómo adaptan otros discursos relacionados en función de sus propios intereses. Se concluye que, si bien hay elementos y conceptos comunes en todos los discursos, estos reflejan demandas diferentes y tensiones entre productores presentes en el territorio, y entre los productores y los organismos públicos. En el caso de las organizaciones campesinas se aborda la escasez hídrica como amenaza a un modo de vida rural, desde el ámbito empresarial se concibe como una amenaza a la producción y exportación de alimentos y, desde los organismos públicos, como un riesgo para la sustentabilidad ambiental, la seguridad y soberanía alimentaria.
Water, To Do What and for Whom?
Keywords: Drought; Water; Agricultural production; Chile; Sequía; Agua; Producción agropecuaria; Chile; https://purl.org/pe-repo/ocde/ford#5.04.00